The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0030344
|View full text |Cite
|
Sign up to set email alerts
|

Nlrp2, a Maternal Effect Gene Required for Early Embryonic Development in the Mouse

Abstract: Maternal effect genes encode proteins that are produced during oogenesis and play an essential role during early embryogenesis. Genetic ablation of such genes in oocytes can result in female subfertility or infertility. Here we report a newly identified maternal effect gene, Nlrp2, which plays a role in early embryogenesis in the mouse. Nlrp2 mRNAs and their proteins (∼118 KDa) are expressed in oocytes and granulosa cells during folliculogenesis. The transcripts show a striking decline in early preimplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 70 publications
9
90
0
Order By: Relevance
“…In our study, all probands with homozygous or compound heterozygous mutations in NRLP2 showed primary infertility and had histories of recurrent IVF/ICSI failure caused by early embryonic arrest. It has been shown in mice that severe reduction in the Nlrp2 protein level lead to lower blastocyst rates and that more embryos are arrested at the two-cell stage 20. The probands in families 1 and 2 who carried homozygous truncating mutations and compound heterozygous truncating and missense mutations in NLRP2 produced very few viable embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all probands with homozygous or compound heterozygous mutations in NRLP2 showed primary infertility and had histories of recurrent IVF/ICSI failure caused by early embryonic arrest. It has been shown in mice that severe reduction in the Nlrp2 protein level lead to lower blastocyst rates and that more embryos are arrested at the two-cell stage 20. The probands in families 1 and 2 who carried homozygous truncating mutations and compound heterozygous truncating and missense mutations in NLRP2 produced very few viable embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it became evident that a novel NLRP2 is expressed in human astrocytes and might have an important role in CNS inflammatory responses similar to the other known NLRPs, since it interacts with the P2 Â 7 receptor and the pannexin-1 channel [40]. Irrespectively of being involved in the inflammatory cascade, NLRP2 was recently discovered in mouse oocytes and granulosa cells during folliculogenesis and described as regulator of early embryogenesis [41]. Knockdown of NLRP2 led to an early embryonic arrest and suggest NLRP2 as a mammalian maternal effect gene required for normal embryonic development.…”
Section: Structure Of Inflammasomes and Sources In The Brainmentioning
confidence: 99%
“…There are no answers to such an overarching question but one glimpse into this quandary may be based in the integration between follicular and oocyte maturation [12]. Structural and physiological studies have now confirmed that a network of cellular interactions mediate critical aspects of oocyte metabolism that have a direct and immediate consequence of postfertilization development of the conceptus [10,13,14] (Fig. 1).…”
Section: Ex Ovo Omniamentioning
confidence: 99%